Konsep Amsal Al-Qur’an Dan Fungsinya Dalam Memahami Makna Ayat - Khoirul Azmi Harahap; Muhammad Idris Rangkuti; Ali Akbar (CV. ITTC INDONESIA, 2026)
Quranic proverbs are one method of conveying divine messages used to facilitate human understanding of the meaning of verses. The parables in the Quran not only function as a beauty of language, but also contain profound educational, reflective, and argumentative values. However, not all readers are able to understand the meaning of proverbs correctly without an adequate scientific approach. This study aims to analyze the concept of Quranic proverbs, their characteristics, and their function in understanding the meaning of verses. This study uses a literature study method (library research) with a descriptive qualitative approach. Data sources in this study consist of books, scientific journals, Quranic commentaries, and other literature relevant to the research topic. The results show that Quranic proverbs have various forms, such as proverbs musarrahah, kaminah, and mursalah, each of which has its own characteristics. In addition, proverbs function to facilitate understanding, strengthen messages, and provide lessons (ibrah) for their readers. Thus, understanding Quranic proverbs is crucial for interpreting verses more deeply, contextually, and with greater applicability to everyday life.